Effect of α-lipoic acid on free radical processes in serum of rats on high fat diet - Marcin Cichoń; Urszula Błaszczyk; Jolanta Zalejska-Fiolka (Nofer Institute of Occupational Medicine, 2017)
Background: Oils are often fried which reduces their beneficial biological and nutritional properties, contributing to disturbances in homeostasis. Some antioxidant substances can improve stability of oils. The aim of the study was to examine the effect of α-lipoic acid (ALA) on the concentration of sulfhydryl groups, lipid peroxides, malondialdehyde, creatinine and urea in serum of rats fed high fat diet for 3 months. Material and Methods: Thirty six Wistar rats were equally divided into 6 groups: the control group on standard breeding diet (SB), oxidized oil (OU) group on SB with 10% oxidized oil, ALA10 group on SB with ALA 10 mg/kg of body weight (b.w.), OU+ALA10 group on SB with oxidized oil and ALA (10 mg/kg b.w.), ALA50 group on SB with ALA in a dose of 50 mg/kg b.w., OU+ALA50 group on SB with oxidized oil and ALA (50 mg/kg b.w.). Oil was oxidized in 180°C for 6 h. Results: We observed decrease in concentration of protein sulfhydryl (PSH) groups in all study groups except for ALA10 vs. control group (C) and increase in OU+ALA10 and OU+ALA50 vs. OU; increase in the lipid hydroperoxide (LHP) concentration in OU, OU+ALA10 and OU+ALA50 vs. C and decrease in all study groups vs. OU; increase of malondialdehyde (MDA) in OU vs. all other groups. And also increase in creatinine and urea concentration in OU group. Conclusions: High fat diet rich in oxidized oil intensifies the lipid peroxidation process and oxidation of sulfhydryl groups. It can also impair kidney function. Administration of lipoic acid in a dose of 10 mg/kg b.w. inhibits the lipid peroxidation and protects sulfhydryl groups. Med Pr 2017;68(3):391-399